Characterization of a structural intermediate of flavivirus membrane fusion. - Karin Stiasny; Christian Kössl; Jean Lepault; Félix A Rey; Franz X Heinz (PLoS Pathogens)
Viral membrane fusion proceeds through a sequence of steps that are driven by triggered conformational changes of viral envelope glycoproteins, so-called fusion proteins. Although high-resolution structural snapshots of viral fusion proteins in their prefusion and postfusion conformations are available, it has been difficult to define intermediate structures of the fusion pathway because of their transient nature. Flaviviruses possess a class II viral fusion protein (E) mediating fusion at acidic pH that is converted from a dimer to a trimer with a hairpin-like structure during the fusion process. Here we show for tick-borne encephalitis virus that exposure of virions to alkaline instead of acidic pH traps the particles in an intermediate conformation in which the E dimers dissociate and interact with target membranes via the fusion peptide without proceeding to the merger of the membranes. Further treatment to low pH, however, leads to fusion, suggesting that these monomers correspond to an as-yet-elusive intermediate required to convert the prefusion dimer into the postfusion trimer. Thus, the use of nonphysiological conditions allows a dissection of the flavivirus fusion process and the identification of two separate steps, in which membrane insertion of multiple copies of E monomers precedes the formation of hairpin-like trimers. This sequence of events provides important new insights for understanding the dynamic process of viral membrane fusion.